(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
The rapid development of digital technologies and artificial intelligence is fundamentally transforming the educational landscape of the twenty-first century. Modern higher education institutions are increasingly integrating intelligent systems, data analytics, and digital platforms into teaching and learning processes. At the same time, global challenges such as climate change, environmental degradation, and the need for sustainable development require a new pedagogical paradigm oriented toward ecological awareness and responsible citizenship. This article examines the role of artificial intelligence in the development of sustainable pedagogy in higher education. The study analyzes the theoretical foundations of digital pedagogy, explores the integration of AI-based educational tools, and highlights their potential for enhancing teaching effectiveness, personalization of learning, and interdisciplinary education. Special attention is given to the formation of ecological thinking and sustainable competencies among students. The research argues that the combination of artificial intelligence technologies with sustainability-oriented pedagogical strategies creates new opportunities for the modernization of education systems. The article proposes conceptual approaches for integrating intelligent digital tools into university curricula while preserving humanistic values and ethical principles of education.